(untitled) (Indonesian Art and Justice Review, 2024)
Representation and inclusion of disabled individuals in the arts are often overlooked, both in terms of access to artistic opportunities and in the portrayal of disability within artistic narratives. This paper explores the issue of disability justice in the Indonesian art scene, focusing on the challenges faced by disabled artists in terms of recognition, accessibility, and opportunities to showcase their work. It also examines how disability is represented in Indonesian art, both by disabled and non-disabled artists, and the extent to which these representations challenge or reinforce societal attitudes toward disability. The paper argues that fostering a more inclusive art environment can help reshape public perceptions of disability and promote justice through greater visibility and participation of disabled artists.